Effects of Celery Seed Extracts on Some Haematological and Biochemical Parameters in Albino Rats Treated with Gentamicin - Tavga Ismael Mustafa; Zhakaw Khudir Abdullah; Nazar Mohammed Shareef Mahmood; Shorish Mustafa Abdullah Gorony; Kurdo Bapir Chato; Ranjbar Muksy Mohammed Shareef (Kurdistan Journal of Applied Research)
The present study targeted the influence of orally celery seeds (Apium graveolens) aqueous extract and ethanolic extracts on male albino rats injected with gentamicin intraperitoneally to investigate some hematological and biochemical parameters. Thirty-two male rats were weighing 300-400 gm carried out for the present research, they controlled environmentally. Animals were divided equally and randomly into four groups each of which contained eight rats. First group (control) included normal rats, group2 were given 100 mg/kg B.W. gentamicin (GM) intraperitoneally (IP), group3 (combined group) were given 100 mg/kg B.W. GM and 150 mg/kg B.W. celery seed ethanolic extract orally by needle gavage, and group4 (combined group) were given 100 mg/kg B.W. GM (IP) and celery seeds aqueous extract 150 mg/kg B.W. orally by needle gavage respectively the present study contiued for eight executive days. The results showed that the elevated by GM haematological parameters  lowered by the celery seed aqueous extract as compared to the celery seed ethanolic extract group, while the elevated serum malondialdehyde (MDA) and total cholesterol (TC) are decreased in group3 more than they were in the group4,  in contrast to that the triglyceride (TG), high density lipoprotein (HDL), low-density lipoprotein (LDL), serum creatinine (CR), serum uric acid (UA), and alkaline phosphatase (ALP) lowered in the group4 from the group 3. The present study concluded that both extracts of celery seeds play a vital biological role, including the improvement effects against the side effect of GM and offering health benefits through decreasing of elevated parameters.